Serological response of patients with influenza A (H1N1) pdm09-associated pneumonia: An observational study - Nasikarn Angkasekwinai (2018)
Background: Little is known about the dynamics or magnitude of antibody response in patients with influenza A (H1N1) pdm09-associated pneumonia. We described and compared the antibody response to influenza A (H1N1) pdm09 in patients with and without pneumonia. Methods: We collected serum samples and determined antibody titers by the hemagglutination inhibition (HI) and microneutralization (mNT) assays from patients with RT-PCR confirmed influenza A (H1N1) pdm09 virus at baseline, 1, 2 and 6 months after onset of illness. Results: Fifty-nine patients were enrolled, 45 (76.3%) were between 15 and 60 years of age, 49 (83.1%) were hospitalized and 25 (42.4%) had complications with pneumonia. Ninety-four percent of patients had HI titers ≥ 1: 40 and 90% had mNT titers ≥ 1: 160 at 2 months after illness. Geometric mean titers (GMT) of HI and mNT increased significantly (p<0.001) between baseline and months 1 or 2, then declined significantly (p<0.001) at month 6 by the HI assay, but dropped to an insignificant level (p=0.24) by the mNT assay. The mNT-GMT was at least twice as high as corresponding HI antibodies over a 6 month period. The GMT of HI and mNT in those with pneumonia (1 mo) peaked earlier than that of those without pneumonia (2 mo). When adjusted by age and gender, those with pneumonia had a higher HI-GMT than those without pneumonia at 1 month (264 vs. 117, p=0.007), 2 months (212 vs. 159, p=0.013), and 6 months (160 vs. 82, p=0.018). Conclusions: The patients recovered from influenza A (H1N1) pdm09-associated pneumonia, clearly developed an earlier and more robust antibody response until 6 months after onset of illness. The results in our study are useful to determine an appropriate donor and timing to obtain convalescent plasma for adjunctive treatment of seriously ill patients with pandemic H1N1 influenza. © 2013 Angkasekwinai et al.